Minimally Invasive Anterior Longitudinal Ligament Release for Anterior Column Realignment. Issue 2 (April 2020) - Godzik, Jakub; Pereira, Bernardo de Andrada; Hemphill, Courtney; Walker, Corey T.; Wewel, Joshua T.; Turner, Jay D.; Uribe, Juan S.
Study Design: Review of the literature. Objectives: Anterior column realignment (ACR) is a powerful but relatively new minimally invasive technique for deformity correction. The purpose of this study is to provide a literature review of the ACR surgical technique, reported outcomes, and future directions. Methods: A review of the literature was performed regarding the ACR technique. A review of patients at our single center who underwent ACR was performed, with illustrative cases selected to demonstrate basic and nuanced aspects of the technique. Results: Clinical and cadaveric studies report increases in segmental lordosis in the lumbar spine by 73%, approximately 10° to 33°, depending on the degree of posterior osteotomy and lordosis of the hyperlordosis interbody spacer. These corrections have been found to be associated with a similar risk profile compared with traditional surgical options, including a 30% to 43% risk of proximal junctional kyphosis in early studies. Conclusions: ACR represents a powerful technique in the minimally invasive spinal surgeon's toolbox for treatment of complex adult spinal deformity. The technique is capable of significant sagittal plane correction; however, future research is necessary to ascertain the safety profile and long-term durability of ACR.